The Impact of Pre-analytic Factors In The Design and Application of Integral Biomarkers for Directing Patient Therapy - Hewitt, Stephen M. (2012)
The use of molecular assays to improve diagnosis have been routinely applied for the last 25 years. Assays that guide therapy have a similar history, however their evolution has lacked the focus on analytic integrity required for the molecularly targeted therapy of today. New molecularly targeted agents require assays of greater precision/quantitation to predict the likelihood of response; identifying patients whose tumors will respond, while at the same time excluding and protecting those patients whose tumors will not respond or treatment will cause unacceptable toxicity. The handling of tissue has followed a “fit-for-purpose” approach focused on appropriateness for diagnostic needs, which is less rigorous than the demands of new molecular assays that interrogate DNA, RNA and proteins in quantitative multiplex assays. There is a new appreciation of the importance and fragility of tissue specimens as the source of analytes to direct therapy. By applying a total test paradigm and defining and measuring sources of variability in specimens, a set of specifications can be developed that can be deployed into the clinical care environment to ensure that a specimen is appropriate for analysis and will return a true result.